Legitimizing Corporate Social Responsibility Through "Huyula" Culture: Melegitimasi Tanggung Jawab Sosial Perusahaan melalui Budaya "Huyula" - Gaffar, Abdul; Gaffar, Muhammad Ichsan; Ibrahim, Melinda; Sukma Nirwana, Nihlatul Qudus (Journal of Accounting Science, 2023)
The study aims to capture the concept of Corporate Social Responsibility (CSR) from the perspectives of Lyotard and Huyula culture. CSR practices serve as a grand narrative used to obtain legitimacy for corporate practices and to mitigate negative impacts. This research adopts a qualitative approach within the framework of Postmodernism. The HUYULA culture is employed to dissect the reality of CSR. The findings of the study reveal that (1) the grand narrative in CSR practices is evident in CSR disclosures that primarily focus on fulfilling CSR item requirements according to GRI guidelines, without considering the actual facts and practices within the company. Moral values are disregarded when cases of environmental exploitation and human exploitation occur. CSR disclosures can serve as a tool for legitimizing the actions of corporate elites in serving their own interests. (2) CSR disclosures that accommodate Indonesian culture and noble values can liberate CSR disclosures from the grand narrative. The values of the Huyula culture can be integrated into CSR practices, making CSR implementation and disclosure tangible expressions of corporate care for stakeholders through a culture of mutual assistance. These values can foster the company's love for its stakeholders. Thus, CSR activities and disclosures go beyond being mere grand narratives. They become acts of corporate compassion towards fellow human beings through local wisdom values. This research provides broad insights and implies that cultural values can serve as the foundation for implementing CSR practices